2018
DOI: 10.1136/gutjnl-2017-314540
|View full text |Cite
|
Sign up to set email alerts
|

Polarised epithelial monolayers of the gastric mucosa reveal insights into mucosal homeostasis and defence against infection

Abstract: Gastric mucosoid cultures faithfully reproduce the features of normal human gastric epithelium, enabling new approaches for investigating the interaction of with the epithelial surface and the cross-talk with the basolateral stromal compartment. Our observations provide striking insights in the regulatory circuits of inflammation and defence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 41 publications
5
113
0
Order By: Relevance
“…Expression of MUC6, a pyloric gland cell marker, was absent in differentiated gastroid monolayers, but was weakly positive in undifferentiated gastroid monolayers (Figure E,F). HGM45 and MUC5AC are the same gastric epithelial and mucin markers, and some previous studies showed that the expression of MUC5AC and MUC6 depended on Wnt3A and RSPO1 . Those studies also mention that withdrawing Wnt‐3A and RSPO1 changed undifferentiated gastroid monolayers (deep basal mucosa) to differentiated ones (gastric surface mucosa).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Expression of MUC6, a pyloric gland cell marker, was absent in differentiated gastroid monolayers, but was weakly positive in undifferentiated gastroid monolayers (Figure E,F). HGM45 and MUC5AC are the same gastric epithelial and mucin markers, and some previous studies showed that the expression of MUC5AC and MUC6 depended on Wnt3A and RSPO1 . Those studies also mention that withdrawing Wnt‐3A and RSPO1 changed undifferentiated gastroid monolayers (deep basal mucosa) to differentiated ones (gastric surface mucosa).…”
Section: Resultsmentioning
confidence: 88%
“…Schlaermann et al described that gastric spheroids constituted an undifferentiated stage and it was possible to differentiate differentiated one by withdrawing Wnt3A and RSPO1. Using their methods, we studied both undifferentiated (with Wnt3A and RSPO1) and differentiated (withdrawal of Wnt3A and RSPO1) gastroid monolayers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations